"It is the innocence which constitutes the crime": Political geographies of white supremacy, the construction of white innocence, and the Flint water crisis. Issue 3 (2nd February 2018) - Inwood, Joshua F.J.
Abstract: Using the Flint, Michigan water crisis as a backdrop, this review piece explores the concept of white innocence. The concept of white innocence presents us with an analytic tool to understand the frustrating endurance of white supremacy within the U.S. settler state and how white supremacy operates through a range of geographically grounded practices. This paper makes an explicit link between work on settler colonialism and white innocence outlining how the burgeoning work on settler societies opens space to a productive engagement with the concept of innocence. I contend that white innocence as a concept needs to be more fully grounded in work that engages with settler colonialism and within the United States specifically. White innocence also inculcates the agency of whites in a society that is built through the explicit exploitation of persons of color as well as the way white institutions continue to expose persons of color to a range of negative impacts. This paper begins with a review of the literature on whiteness within geographic research. The last several years has seen a series of important interventions in the literature and geographers are increasingly turning to the concept of white supremacy to explain racism in 21st century U.S. society.